Incidental gonadal germ cell tumours at the time of prophylactic gonadectomy in patients with Swyer syndrome - a report of 3 cases - Basheska, Neli; Ognenoska-Jankovska, Biljana; Veljanoska, Slavica; Plasheska-Karanfilska, Dijana (Springer, 2018)
Background & Objective: Swyer syndrome (46,XY pure gonadal dysgenesis) is an uncommonly encountered condition in which gonadectomy is recommended upon diagnosis due to a significant risk of malignant transformation of the dysgenetic gonads. The aim of this study was to present our experience with incidentally found germ cell tumours in patients with Swyer syndrome. Method: We report the clinico-pathological characteristics of 3 cases of female phenotypic patients presenting with primary amenorrhea who underwent prophylactic bilateral laparoscopic gonadectomy with salpingectomy following a diagnosis of Swyer syndrome. At the time of diagnosis, they were 17 to 20 years old. The presenting features were hypogonadotropic hypogonadism and 46, XY karyotype. A hypoplastic uterus with normal looking fallopian tubes and bilateral gonads were detected by ultrasonography and confirmed during laparoscopy. The patients with dysgerminoma underwent postoperative chemotherapy. All three patients are alive and well 70, 115 and 144 months following surgery. Results: The histopathological examination of the streak gonads which were completely sampled and embedded revealed the presence of bilateral predominantly “burnt out” gonadoblastoma in all patients. In addition, in two patients, a coexisting dysgerminoma of 1.5 and 3.8 cm in diameter FIGO stage IC1 in the right gonad was confirmed. The sequencing of the SRY gene of the patient with bilateral gonadoblastoma without dysgerminoma overgrowth revealed a C/G substitution at the first nucleotide of codon 133, leading to Arg/Gly replacement in the SRYprotein. Conclusion: Our data suggest that patients with gonadal dysgenesis and 46, XY karyotype should be referred for bilateral gonadectomy and their operative specimens should undergo meticulous histopathological examination because of the high risk of neoplastic transformation.
Keywords: Swyer syndrome; 46,XY pure gonadal dysgenesis; germ cell tumour; gonadoblastoma; dysgerminoma